Penggunaan Literatur dalam Penulisan Karya Ilmiah Mahasiswa Agroteknologi Instiper Yogyakarta (Studi Bibliometrika pada Jurnal Agromast Tahun 2018-2019) - Laylatul Munawaroh; Marwiyah Marwiyah (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2020)
This study aims to determine the dominance of reference sources, types of references, the most cited authors, the availability of collections in the Stiper Institute of Agriculture (Instiper) library and the reference year used by students in preparing scientific papers. This study uses a quantitative descriptive approach and bibliometric studies with citation analysis and literary life half-life. The object of analysis in this research is 166 scientific articles published in the journal Agromast published in 2018-2019. The results showed that: 1) types of reference sources or information materials used as references for students in writing scientific papers were dominated by types of references in the form of books (74.90%) and scientific articles (16.10%). 2) The half-life age of the literature cited in the journal Argomast as a whole from 2018 to 2019 is 8 years. 75.59% of the literature that is considered up-to-date or obsolete, while the literature that is considered current is 28.15%. Thus, the literature used as a reference in the Agromast journal 2018-2019 tends to use less up-to-date literature.